Weighted integral representations of harmonic functions in the unit disc by means of Mittag-Leffler type kernels - Hayrapetyan, Feliks (Armenian Journal of Mathematics, 2021)
For weighted $L^p$-classes of functions harmonic in the unit disc, we obtain a family of weighted integral representations with weight function of the type $|w|^{2φ}·(1-|w|^{2ρ})^{β}$.
Keywords: Harmonic Functions in the Unit Disc; Weighted Function Space; Weighted Integral Representation